Use of complementary and alternative medicine among females with polycystic ovary syndrome in Jordan: a cross-sectional study - Oriana Awwad; Mais Saleh; Ali Alsamydai; Fatma U Afifi; Amal Akour; Renad Abu Tarboosh; Manar Hamdan; Asma Sa’d Basha; Sanaa K Bardaweel (BMJ Open, 2024)
Background and objectives Polycystic ovary syndrome (PCOS) is a prevalent female reproductive and metabolic disorder. Among patients with chronic conditions, an increasing number have approached complementary and alternative medicine (CAM) to cope with their disease. This study aimed to assess the use of CAM among females with PCOS in Jordan.Design, settings and participants A cross-sectional study was conducted at one of the largest tertiary centres in Jordan. Adult females with PCOS were interviewed using a data collection tool.Outcome measures CAM use and the factors associated with its use.Results A total of 402 women participated in the study, the median-IQR age was 25 (31–21) years. Common PCOS signs/symptoms included menses irregularity (81.8%), fatigue (71.6%) and hyperandrogenism (77.6%). Among all participants, 63.2% used CAM with the most common being herbs (60.4%). The primary sources of information were family and friends (46.1%).Longer duration since diagnosis, having more PCOS signs/symptoms and a higher level of education were factors significantly associated with CAM use (β=1.257, 95% CI=1.018 to 2.552, p=0.034; β=1.146, 95% CI=1.052 to 1.250, p=0.002 and β=1.584, 95% CI=1.054 to 2.379, p=0.027, respectively). Of all the CAM users, 57.5% reported an amelioration in PCOS symptoms; this was significantly associated with the long-term use of CAM (β=12.759, 95% CI=6.789 to 23.976, p<0.001). Just a few participants (9.4%) reported side effects.Conclusion A variety of CAM approaches were reported by the study population; herbs were the most widely used and accepted by the patients. Considering the primary source of information and the potential interactions of herbal medicine with the standard PCOS treatment, efforts are needed by healthcare providers to better understand the use of CAM among their patients with PCOS.